Decoding Student Struggles in Geometry: Newman Error Analysis of Higher-Order Thinking Skills - Kania, Nia; Kusumah, Yaya S.; Dahlan, Jarnawi Afgani; Nurlaelah, Elah; Kyaruzi, Florence (EDUPEDIA Publisher, 2024)
Maths is one of the most challenging courses for many pupils. Maths is often the most complex subject for many students. Newman's Error Analysis analyses eighth-graders math problems. Assessing higher-order cognitive ability is the primary purpose. This qualitative study was conducted in a Majalengka, West Java, junior high. Five randomly selected kids with different math skills participated. Following up with interviews and testing Bloom's taxonomy's latest HOTS signal questions were the critical data collection approaches. These questions test analytical (C4), evaluative (C5), and creative (C6) skills. Students had to model, sketch, confirm geometric calculations, and calculate dimensions using available components. Newman's Error Analysis was applied to analyse typical misunderstandings and errors. This exercise showed students' geometric reasoning and problem-solving weaknesses. The findings suggest customised teaching methods to improve students' geometric knowledge and performance. Reducing data, presenting facts, and concluding helped us comprehend pupils' cognitive processes and geometric challenges.